LINDENBERGIA LEHM. (OROBANCHACEAE): A NEW GENERIC RECORD IN JAVA AND BORNEO - AL FARISHY, DEE DEE; TIANARA, ALEXANDER; MUSTAQIM, WENDY ACHMMAD (Research Center for Biology, 2024)
The genus Lindenbergia Lehm. is reported for the first time in Java, Indonesia, where Lindenbergia philippensis (Cham. & Schltdl.) Benth. was recently collected from the lowland area of Depok and Jakarta, northwest Java. The genus is also known to be collected in Borneo after literature examinations. Description, distribution map, identification key, note, and photographs of the species are given alongside a discussion of the occurrence status of the genus and species. A key to all six genera of Orobanchaceae in Java is also given accompanied by a list of all currently accepted species